YOUTH CULTURE AND PHYSICAL EDUCATION IN THE CONTEXT OF A PUBLIC SCHOOL: A CASE STUDY (Fiep Bulletin - online, 2011)
Since the beginning of my teaching practice as a physical education teacher, I realize that young adolescents are encouraged to practice the sport of income. In most cases, they have opportunities to experience other cultures. There is a wide gap between the world of school - with its know-rules and procedures - and the world of young people with their experiences and interests. The goal is to know with the youth cultures circulate in the school environment and how they are "read" by students and teachers. Looking still making a connection between these cultures and the curricular proposals in his political teaching. The authors defined so that the study are Bracht, Dayrell, Corti, Canclini. The research will be qualitative in nature, guided by the methodology of case study in a municipal school of Belo Horizonte / MG. In mining the information will be used observations of classes, the school spaces, groups of cultures, with semi-structured interviews, photographs, film and video analysis. I noticed that there is a mismatch between school culture and teen culture. This gap is manifested in the requirement that the school places for students through its rules and taxes. Rules which require to be met many times that the adolescent desvista "identity. In the community, there is a large movement of groups of capoeira, hip-hop, forró, graffiti, circus, crafts, congado, folia de reis, etc. Who are appropriating public spaces, between the school and seek dialogue with all actors of these spaces, showing that it can and should be a vehicle of communication to other spaces.
Keywords: Youth Cultures; Physical Education; School